High-strength aluminum-magnesium layered composite material and preparation method thereof
Through the combination technology of multi-pass friction stir processing and cold rolling, the problem of low interface bonding strength of aluminum-magnesium layered composite materials is solved, high strength and good elongation are achieved, and materials are met in aerospace, automobile manufacturing and other fields. application requirements.
Patent Information
- Application Number
- CN202411540541.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
AI Technical Summary
The low interface bonding strength of existing aluminum-magnesium layered composite materials leads to instability in microstructure and performance, limiting the development and application of materials.
The combination technology of multi-pass friction stir processing and cold rolling is used to form a pre-bound layered composite material, and the interface bonding strength is enhanced through heat treatment.
It significantly improves the tensile strength and shear strength of aluminum-magnesium layered composite materials, improves the interface bond strength and deformation coordination, and meets the needs of lightweight, high strength and good elongation.
Smart Images

Figure CN119457388A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal materials, and in particular relates to a high-strength aluminum-magnesium layered composite material and a preparation method thereof. Background Art
[0002] Magnesium alloys have the characteristics of high specific strength and strong impact load resistance, but are susceptible to corrosion. Aluminum alloys have excellent corrosion resistance and formability. Therefore, aluminum-magnesium layered composites characterized by lightweight, high strength, and corrosion resistance are widely used in aerospace, automobile manufacturing, and electronics.
[0003] Traditional methods for preparing layered composite materials mainly include cold rolling composite method, explosive composite method, diffusion composite method and friction stir composite method. Although explosive composite can obtain a wavy interface with high bonding strength, it has some disadvantages, such as high preparation risk, serious environmental pollution, brittle interface metal compounds and difficulty in ensuring the stability of material properties. In addition, diffusion welding has low bonding strength and Kirkenda ll holes are easily generated at the interface. Cold rolling composite method is simple to operate, suitable for large-scale production, and can refine and homogenize the microstructure of the composite material. However, when heterogeneous metals with different physical and chemical properties are cold rolled, the interface bonding strength is not high, which seriously limits the overall performance of the sheet. Friction stir processing can refine and densify the local microstructure of the composite material and form a wavy interface similar to explosive composite. However, for composite materials, the refinement of the local microstructure cannot meet the actual production needs. In the preparation stage, due to the differences in physical and chemical properties and crystal structure between aluminum and magnesium, brittle metal compounds are easily formed at the interface, which will seriously affect the interface bonding strength and limit the development and application of aluminum-magnesium layered composite materials. Therefore, the above-mentioned single preparation technology cannot effectively solve the problems of weak interface bonding, microstructure and performance of aluminum-magnesium layered composites. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to provide a high-strength aluminum-magnesium layered composite material and a preparation method thereof, so as to solve the problems of weak interface bonding, microstructure and performance of aluminum-magnesium layered composite materials prepared by existing methods.
[0005] To achieve the above object, the technical solution adopted by the present invention includes:
[0006] A method for preparing a high-strength aluminum-magnesium layered composite material comprises the following steps:
[0007] First, an aluminum alloy plate is selected as the upper material, and a magnesium alloy plate is selected as the lower material, and the upper material and the lower material are spliced up and down to obtain a two-layer structure;
[0008] Secondly, the two-layer structure is subjected to multiple friction stir processing to form a pre-bonded layered composite material;
[0009] Finally, the pre-bonded layered composite material is cold rolled and heat treated to obtain a high-strength aluminum-magnesium layered composite material.
[0010] Preferably, the aluminum alloy plate is 2024Al alloy or 7075Al alloy, and the magnesium alloy plate is AZ31B magnesium alloy or AZ61 magnesium alloy.
[0011] Preferably, the multi-pass friction stir processing is to compound the upper layer material and the lower layer material with different shoulder overlap rates, and the overlap rate between the shoulder of the previous pass and the shoulder of the next pass is 0% to 30%.
[0012] Preferably, the overlap rate between the shoulder of the previous pass and the shoulder of the next pass in the multi-pass friction stir processing is 25%.
[0013] Preferably, the thickness of the aluminum alloy plate is 2-5 mm, and the thickness of the magnesium alloy plate is 2-5 mm.
[0014] Preferably, the stirring head for multi-pass friction stir processing is made of H13 tool steel, the stirring needle length is 2.0 mm, the shoulder width is 18 mm, the rotation speed is 800 r / min, and the processing speed is 40 mm / min.
[0015] Preferably, the pre-bonded layered composite material needs to be preheated before cold rolling, the preheating temperature is 350-380° C., and the preheating time is 8-10 minutes.
[0016] Preferably, the cold rolling is a single cold rolling, and the cold rolling reduction is 45%.
[0017] Preferably, the heat treatment subsequent to cold rolling is a low-temperature annealing heat treatment at 150° C., and the annealing time is 30 to 120 minutes.
[0018] A high-strength aluminum-magnesium layered composite material is prepared by the preparation method of the high-strength aluminum-magnesium layered composite material disclosed in the present application. The prepared high-strength aluminum-magnesium layered composite material has a tensile strength of 290-310 MPa and a room temperature shear strength of 116-146 MPa.
[0019] Compared with the prior art, the present invention has the following technical effects:
[0020] 1. A high-strength aluminum-magnesium layered composite material and a preparation method thereof of the present invention, through a combination technology of multi-pass stir friction processing + cold rolling, utilizes cold rolling to crush the hard and brittle intermetallic compounds produced in the stir friction processing stage, increases the interface bonding area, enables the composite material to maintain good coordination and continuity of each layer during the deformation process, reduces the loss of plasticity of the composite material during the preparation process, and obtains a high-performance aluminum-magnesium layered composite material.
[0021] 2. A high-strength aluminum-magnesium layered composite material and a preparation method thereof of the present invention obtain a "wave" shaped interface similar to that obtained by the explosive composite method without affecting the environment, which greatly improves the shear strength of the composite material, and the maximum shear strength can reach 146MPa. At the same time, the improvement of the interface bonding strength helps to improve the deformation coordination of the composite material, so that the tensile strength of the composite material is also greatly improved. While the tensile strength reaches 303MPa, it can also maintain an elongation of 13.4%.
[0022] 3. The high-strength aluminum-magnesium layered composite material and the preparation method thereof of the present invention can be produced on a large scale by the selected preparation technology, is suitable for industrial production, and reduces the production cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a schematic diagram of the preparation process of the present invention;
[0024] Figure 2 is a SEM image of the interface of the cold-rolled composite material prepared by the present invention;
[0025] Figure 3 It is the engineering stress-strain curve of the aluminum-magnesium layered composite material prepared by the present invention;
[0026] Figure 4 It is a bar graph of the shear strength of the aluminum-magnesium layered composite material prepared by the present invention. DETAILED DESCRIPTION
[0027] In the present invention, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways, such as by addition, deletion, modification, etc., without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature. The specific embodiments of the present invention are described in detail below in conjunction with the drawings. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention.
[0028] The friction stir processing in the present invention is a severe plastic deformation processing technology. It is a high-speed rotation of the stirring head into the material to be processed until the shoulder contacts the material to be processed. Since the stirring needle is in a high-speed rotation state, the friction between the shoulder and the material generates a large amount of heat and causes the material to soften, and moves forward along the processing direction at a certain speed. In the processing area, the material undergoes severe plastic deformation under the action of the stirring needle, and the structure is refined. Multi-pass friction stir processing is a processing method for preparing composite materials derived from it.
[0029] The optimization of the present invention is to rationally combine different composite material preparation processes to better control the interface bonding and performance improvement of the composite material, and improve the deformation coordination and comprehensive mechanical properties of the material. Figure 1 As shown, the present invention determines the aluminum alloy plate, magnesium alloy plate and thickness according to the performance requirements of interface bonding, and designs a layered composite material by combining multiple preparation process ideas, and then obtains the layered composite material through multiple stir friction processing pre-bonding and subsequent cold rolling process.
[0030] Embodiment 1:
[0031] This embodiment provides a method for preparing a high-strength aluminum-magnesium layered composite material, wherein an aluminum alloy plate and a magnesium alloy plate are stacked to form a layered structure, and the layered structure is subjected to multiple friction stir processing and cold rolling to obtain a high-strength aluminum-magnesium layered composite material.
[0032] In this embodiment, an aluminum alloy plate (2024-T4) with a thickness of 2 mm and a magnesium alloy plate (AZ31 B) with a thickness of 2 mm are specifically selected and stacked in the form of 2024A l(2mm) / AZ31 B(2mm).
[0033] The specific steps include:
[0034] Step 1: Surface treatment is performed on the aluminum alloy plate and the magnesium alloy plate, and then the two-layer structure is obtained by stacking and splicing them in sequence; the surface treatment is specifically to grind the aluminum alloy and magnesium alloy plates with a grinder to remove the surface oxide layer until the fresh metal is exposed, wash the surface impurities with alcohol, and then ultrasonically clean them in an acetone solution for 10 minutes and wrap them with plastic wrap for use;
[0035] Step 2: performing multiple friction stir processing on the two-layer structure obtained in step 1 to form a pre-bonded layered composite material;
[0036] The stirring head for multi-pass friction stir processing is made of H13 tool steel, the stirring needle length is 2.0mm, the shoulder width is 18mm, the rotation speed is 800r / min, the processing speed is 40mm / min, and the plate is compounded with different shoulder overlap rates, that is, the overlap rate between the previous shoulder and the next shoulder is 0% (shoulder overlap 0mm) to 30% (shoulder overlap 5.4mm), and the overlap rate of this embodiment is 0%.
[0037] Step three, cold rolling and heat treatment of the pre-bonded layered composite material obtained in step two to obtain a high-strength aluminum-magnesium layered composite material.
[0038] The cold rolling preheating temperature is 350°C, and the preheating time is 10 minutes; the cold rolling is a single cold rolling, and the cold rolling reduction is 45%; the subsequent heat treatment of the cold rolling is a low-temperature annealing heat treatment at 150°C, and the annealing time is 30 minutes.
[0039] Through process annealing treatment, the performance of the composite plate is improved to facilitate subsequent processing; the interface diffusion between heterogeneous material layers is promoted to form a stable metallurgical bond and improve the interface bonding strength; and the processing stress inside the composite plate is reduced.
[0040] In this embodiment, a high-strength aluminum-magnesium layered composite material was successfully prepared, with a tensile strength of about 300 MPa and a shear strength of 133 MPa, which are much higher than the 20-30 MPa of general aluminum-magnesium layered composite materials.
[0041] Figure 2 This is a SEM image of the interface of the cold-rolled composite material prepared by the present invention. It can be seen from the figure that the composite materials with different parameters all maintain good continuity, the broken intermetallic compounds at the interface are tightly combined with the matrix, and no voids and interface cracks are observed, indicating that the interface of the composite plate is well combined.
[0042] Figure 3 The engineering stress-strain curve of the aluminum-magnesium layered composite material prepared by the present invention; it can be observed from the figure that the composite material has excellent strength (303MPa)-plasticity (13.4%) matching under the parameters of overlap rate 25% and heat treatment time 60min. The composite material prepared in this embodiment meets the requirements of lightweight, high strength, good elongation, etc.
[0043] Figure 4 This is a bar graph of the shear strength of the aluminum-magnesium layered composite material prepared by the present invention. It can be seen from the figure that the shear strength of the composite material is greater than 100 MPa, that is, the composite material has extremely strong interface bonding strength.
[0044] Embodiment 2:
[0045] Other conditions of this embodiment are the same as those of embodiment 1, except that the shoulder overlap rate of the multi-pass friction stir processing is 25%. The tensile strength of the composite material obtained in this embodiment is about 315 MPa, and the average shear strength of the product is about 116 MPa.
[0046] Example 3
[0047] This embodiment is the same as embodiment 1, except that the annealing heat treatment holding time is 60 minutes. The tensile strength of the composite material obtained in this embodiment is about 299 MPa, and the average shear strength of the product is about 146 MPa.
[0048] Example 4
[0049] This embodiment is the same as Embodiment 1, except that the shoulder overlap rate of the multi-pass stir friction processing is 25%, and the annealing heat treatment holding time is 60 minutes. The tensile strength of the product obtained is about 303 MPa, the elongation is about 13.4%, and the average shear strength of the product is about 123 MPa.
[0050] Comparative Example 1
[0051] The difference between Comparative Example 1 and Example 1 is that only multiple stir friction processing is performed, and subsequent cold rolling and heat treatment are no longer performed.
[0052] Almost all the samples prepared in Comparative Example 1 showed delamination and fracture. This was mainly because the large amount of heat input brought about by the multiple-pass stir friction processing caused the aluminum and magnesium elements to diffuse violently, and a large amount of brittle intermetallic compounds were produced at the interface, resulting in weak bonding and a tensile strength of about 250 MPa.
[0053] Comparative Example 2
[0054] The difference between Comparative Example 2 and Example 1 is that the 2024A1 and AZ31B materials are hot pressed and sintered and rolled to obtain a composite material.
[0055] The shear strength of the sample obtained in Comparative Example 2 is only 27MPa. This is because the Al-Mg layered composite material exhibits multi-stage fracture characteristics during tensile loading, that is, the I MC layer at the interface fractures first, then the Mg matrix fractures, and finally the Al matrix fractures. Among them, the Mg matrix fractures by transgranular cleavage, and the Al matrix fractures by dimples. In the shear test, the Al / Mg interface exhibits brittle cleavage fracture, and the fracture position is located between the Al3Mg2 phase layer and the Mg 32 A l 47 Between Cu7 phase layers.
[0056] Comparative Example 3
[0057] The difference between Comparative Example 3 and Example 1 is that only vibration-assisted rolling is performed on the material to obtain the composite material.
[0058] The shear strength of the sample obtained in Comparative Example 3 is about 46MPa. During the vibration-assisted rolling process, the vibration of the roller along the TD direction forces the metal flow direction to change, which increases the flow of the metal in the TD direction, and the oxide film and the hardened layer form a criss-cross crack morphology. It increases the contact area of the fresh metal, reduces the cutting effect at the interface, and promotes the strong metallurgical bonding of the interface to a certain extent. However, due to the non-wavy interface of the overall material interface, the strong metallurgical bonding effect brought by vibration-assisted rolling is limited.
[0059] In summary, it can be seen that it is difficult to meet the industry's demand for high-performance materials by improving material performance through a single preparation process. On the basis of rationally adding multiple preparation processes, the material is rationally designed in structure and process to obtain a high-strength aluminum-magnesium layered composite material.
Claims
1. A method for preparing a high-strength aluminum-magnesium layered composite material, characterized in that: The following steps are involved: First, an aluminum alloy plate is selected as the upper material, and a magnesium alloy plate is selected as the lower material, and the upper material and the lower material are spliced up and down to obtain a two-layer structure; Secondly, the two-layer structure is subjected to multiple friction stir processing to form a pre-bonded layered composite material; Finally, the pre-combined layered composite material is cold rolled and heat treated to obtain a high-strength aluminum-magnesium layered composite material.
2. The method for preparing the high-strength aluminum-magnesium layered composite material according to claim 1, characterized in that: The aluminum alloy plate is 2024Al alloy or 7075Al alloy, and the magnesium alloy plate is AZ31B magnesium alloy or AZ61 magnesium alloy.
3. The method for preparing the high-strength aluminum-magnesium layered composite material according to claim 2, characterized in that: The multi-pass friction stir processing is to compound the upper layer material and the lower layer material with different shoulder overlap rates, and the overlap rate between the upper shoulder and the next shoulder is 0% to 30%.
4. The method for preparing the high-strength aluminum-magnesium layered composite material according to claim 3, characterized in that: The multi-pass friction stir processing specifically has an overlap rate of 25% between the shoulder of the previous pass and the shoulder of the next pass.
5. The method for preparing the high-strength aluminum-magnesium layered composite material according to any one of claims 1 to 4, characterized in that: The thickness of the aluminum alloy plate is 2-5 mm, and the thickness of the magnesium alloy plate is 2-5 mm.
6. The method for preparing the high-strength aluminum-magnesium layered composite material according to any one of claims 1 to 4, characterized in that: The stirring head for multi-pass friction stir processing is made of H13 tool steel, with a stirring needle length of 2.0 mm, a shoulder width of 18 mm, a rotation speed of 800 r / min, and a processing speed of 40 mm / min.
7. The method for preparing the high-strength aluminum-magnesium layered composite material according to any one of claims 1 to 4, characterized in that: Before cold rolling, the pre-bonded layered composite material needs to be preheated, the preheating temperature is 350-380° C., and the preheating time is 8-10 minutes.
8. The method for preparing the high-strength aluminum-magnesium layered composite material according to any one of claims 1 to 4, characterized in that: The cold rolling is a single-pass cold rolling with a cold rolling reduction of 45%.
9. The method for preparing the high-strength aluminum-magnesium layered composite material according to any one of claims 1 to 4, characterized in that: The subsequent heat treatment of cold rolling is a low-temperature annealing heat treatment at 150°C, and the annealing time is 30 to 120 minutes.
10. A high-strength aluminum-magnesium layered composite material, characterized in that: The high-strength aluminum-magnesium layered composite material is prepared by the preparation method of any one of claims 1 to 9. The prepared high-strength aluminum-magnesium layered composite material has a tensile strength of 290 to 310 MPa and a room temperature shear strength of 116 to 146 MPa.
Citation Information
Patent Citations
Method for manufacturing high-strength laminated composite boards
CN103286434A
Aluminum magnesium alloy composite board and preparing method thereof
CN108687159A
High-strength, high-plasticity and anti-corrosion aluminum alloy laminated composite material and manufacture method thereof
CN110665968A
High-strength wear-resistant anti-corrosion aluminum / magnesium heterogenetic connector and preparation method thereof
CN111660007A
Method for preparing ultrathin aluminum-magnesium layered composite material through low-temperature rolling
CN112828037A
Cited By
Copper-aluminum-magnesium composite material and preparation method and application thereof
CN120438577A